(untitled) (ARQUISUR Revista, 2012)
The urban sprawl in Santa Fe city (Argentina) along the East side, in the Paraná river´s flooding valley, it is an interesting analysis case among a wide range of bibliography which, in the last decades, has been dedicated to suburban problematic. It was about a process which principally took place since the state of neglect (physical and political) in which the area stayed for a great part of XX century; and which finally was empower, in 1959, by the urban legal regime repealing. That was a transition (which started at the endings of XIX century) from a conception of periphery as the production place, or extractive exploitation place, to another one related to the urban inhabitant´s confort. Both processes were the hinge which leaded to an exponential consumption of periurban space, by an intense residential occupation; process by which the periphery, paradoxically, acquired centrality. By that way, because of the legal exception, it would be urbanized a hydric critical zone whose principal natural function is to control the river´s regime, and whose capacity for supporting urban dynamics, because of its typical characteristics, is considerably limited.